Oxidation of 2′-Deoxyadenosine 5′-Monophosphate Photoinduced by Lumazine - Denofrio, Maria Paula (2010)
UV radiation induces damages to the DNA molecule and its components through photosensitized reactions. Among these processes, photosensitized oxidations may occur through electron transfer or hydrogen abstraction (type I mechanism) and/or the production of singlet molecular oxygen (1 O2) (type II mechanism). Lumazines are an important family of heterocyclic compounds present in biological systems as biosynthetic precursors and/or products of metabolic degradation. To evaluate the capability of lumazines to act as photosensitizers through type I mechanism, we have investigated the oxidation of 2′-deoxyadenosine 5′-monophosphate (dAMP) photosensitized by the specific compound called lumazine (pteridine-2,4(1,3H)-dione; Lum) in aqueous solutions under UV irradiation. The photochemical reactions were followed by UV/vis spectrophotometry, HPLC, electrochemical measurement of dissolved O2, and an enzymatic method for H2O2 determination. The effect of pH was evaluated and the participation of oxygen was investigated. In aerated solutions, oxidation of dAMP photoinduced by the acid form of Lum (pH 5.5) takes place through a type I mechanism, in which the excitation of Lum is followed by an electron transfer from dAMP molecule to the Lum triplet excited state. During the process, O2 is consumed and H2O2 is generated, whereas the photosensitizer is not consumed. In contrast, no evidence of a photochemical reaction induced by the basic form of Lum (pH 10.5) was observed.